Redescription of Draposa subhadrae (Patel & Reddy, 1993) (Araneae: Lycosidae, Pardosinae) - Marusik, Yuri M.; Omelko, Mikhail M. (Zootaxa, 2016)
Draposa Kronestedt, 2010 is a small genus of Pardosinae spiders. Currently it encompasses 10 species (World Spider Catalog 2016) distributed from Pakistan to Southeast China. Most species of the genus, except for D. porpaensis (Gajbe, 2004), are known from both sexes and were described or redescribed by Kronestedt (2010). Two other species, D. amkhasensis (Tikader & Malhotra, 1976) and D. burasantiensis (Tikader & Malhotra, 1976), both recently transferred to Draposa (Dhali et al. 2012 ), are doubtful because their copulatory organs are not properly illustrated and differ from the type species and other species of the genus. The male of Draposa subhadrae (Patel & Reddy, 1993) remains known by very poor original drawings because Kronestedt (2010) was not able to study types. While studying material from Sri Lanka collected by us, we found one sample with two females belonging to D. subhadrae and two males of Draposa having the same colour pattern and size. We concluded that these specimens are conspecific. The goal of this paper is to provide an illustrated redescription of this species.